2004
DOI: 10.1116/1.1821571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coulomb effects on electron projection lithography process

Abstract: Articles you may be interested inInfluence of proximity effects in electron-beam lithography on the optical properties of planar photonic-crystal waveguides J. Appl. Phys. 102, 083110 (2007); 10.1063/1.2801023 Direct measurements and analyses of the Coulomb effects in electron projection lithographya) J. Vac. Sci. Technol. B 23, 3182 (2005); 10.1116/1.2131085 Resolution-limiting factors in low-energy electron-beam proximity projection lithography: Mask, projection, and resist process J. Vac. Sci. Technol. B 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…2 Our direct measurement of beam blur distribution in a SF clearly revealed that the beam blur depended not only on the beam current but also on spatial pattern arrangement including local Coulomb effects. In electron projection lithography ͑EPL͒, 1 mask bias method is used for PEC because the subfield ͑SF͒, where a flat exposure dose is given, is much larger ͑250 m square on wafer͒ than an electron backscattering range of about 32 m for 100 keV electron beam.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…2 Our direct measurement of beam blur distribution in a SF clearly revealed that the beam blur depended not only on the beam current but also on spatial pattern arrangement including local Coulomb effects. In electron projection lithography ͑EPL͒, 1 mask bias method is used for PEC because the subfield ͑SF͒, where a flat exposure dose is given, is much larger ͑250 m square on wafer͒ than an electron backscattering range of about 32 m for 100 keV electron beam.…”
Section: Introductionmentioning
confidence: 74%
“…The data processing is executed using a 10 PC cluster system. 2 Because the SCEC program solves a Poisson's equation to correct for the space charge effect, it takes a long time to do the calculation. Then, the process proceeds to PEC, followed by the mask layout and design rule check and verification.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, 6 we observed the possibility of the local Coulomb effects because the blur in SF depended on the pattern arrangements even when the patterns were printed with the same beam current. This led us to investigate the local Coulomb effects.…”
Section: Local Coulomb Effectsmentioning
confidence: 90%
“…In general, increasing beam current density will degrade beam resolution due to the Coulomb interaction effects. 30,[52][53][54][55][56] This will be addressed by optimizing the electron optical parameters that affect the effects. Optimizing writing strategy including the PLDC, which is related with M s and B b , is also a key element.…”
Section: Future Of Mbm Seriesmentioning
confidence: 99%